Impairment of decision making associated with disruption of phase-locking in the anterior cingulate cortex in viscerally hypersensitive rats - Cao, Bing; Wang, Jun; Mu, Li; Poon, David Chun-Hei; Li, Ying (Experimental neurology, 2016)
Visceral hypersensitivity (VH) is a key factor of irritable bowel syndrome (IBS). Previous studies have identified an enhanced response of anterior cingulate cortex (ACC) to colorectal distension in VH rats, which can be observed up to 7weeks following colonic anaphylaxis, independent of colonic inflammation. The induction of VH produces a change in the ability to induce subsequent synaptic plasticity at the ACC circuitry. In clinical practice, a positive link between IBS and cognitive impairments has been noted for years, but no animal model has been reported. Decision-making is a valuable model for monitoring higher-order cognitive functions in animals, which depends on the integrated function of several sub-regions of the ACC and amygdala. Using rat gambling task (RGT) in the present study, we observed an impairment of decision-making behavior in VH rats. Electrophysiological study showed a reduction of long-term potentiation in the basolateral amygdala (BLA)-ACC synapses in VH rats. Multiple-electrode array recordings of local field potential (LFP) in both BLA and ACC were also performed in freely behaving rats. Spike-field coherence (SFC) analysis revealed chronic visceral pain led to disruption of ACC spike timing and BLA local theta oscillation. Finally, cross-correlation analysis revealed that VH was associated with suppressed synchronization of theta oscillation between the BLA and ACC, indicating reduced neuronal communications between these two regions under the VH state. The present results demonstrate that functional disturbances in BLA-ACC neural circuitry may be relevant causes for the deficits in decision-making in chronic pain state. •Visceral hypersensitivity (VH) induces decision making deficits in rat.•Synaptic plasticity is impaired in the BLA-ACC network of VH rats.•VH disrupts phase locking of ACC spikes to BLA theta oscillations.•Theta band synchronization between ACC and BLA is decreased in VH rats.